2006
DOI: 10.1103/physrevlett.96.075002
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Turbulent Spectra in the Terrestrial Magnetosheath as Seen by the Cluster Spacecraft

Abstract: Here we report the first three-dimensional spatial spectrum of the low frequency magnetic turbulence obtained from the four Cluster spacecraft in the terrestrial magnetosheath close to the magnetopause. We show that the turbulence is compressible and dominated by mirror structures, its energy is injected at a large scale kp approximately 0.3 (l approximately 2000 km) via a mirror instability well predicted by linear theory, and cascades nonlinearly and unexpectedly up to kp approximately 3.5 (l approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
234
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(264 citation statements)
references
References 19 publications
21
234
1
Order By: Relevance
“…Instead there appears to be a limit on how turbulent these fluctuations can be whether it is due to a limit on the number of modes associated with the fluctuations (as is thought to be the case in the LAPD [15]) or whether there is a limit on how much power can be distributed to higher frequencies (or smaller scales). In SSX, this latter issue may arise due to boundary or temporal development limits, both of which are not encountered by solar wind plasma (but may be relevant for the more bounded turbulent system of the magnetosheath [38,39], for example). The results of the CH plane analysis highlight that more work is needed to push laboratory plasma turbulence research into the fully developed regime.…”
Section: Ch Comparison Of Ssx Wind and Lapd Datamentioning
confidence: 99%
“…Instead there appears to be a limit on how turbulent these fluctuations can be whether it is due to a limit on the number of modes associated with the fluctuations (as is thought to be the case in the LAPD [15]) or whether there is a limit on how much power can be distributed to higher frequencies (or smaller scales). In SSX, this latter issue may arise due to boundary or temporal development limits, both of which are not encountered by solar wind plasma (but may be relevant for the more bounded turbulent system of the magnetosheath [38,39], for example). The results of the CH plane analysis highlight that more work is needed to push laboratory plasma turbulence research into the fully developed regime.…”
Section: Ch Comparison Of Ssx Wind and Lapd Datamentioning
confidence: 99%
“…Two main similarities with solar wind turbulence emerged from those studies: the turbulence in strongly anisotropic (k k ⊥ ) at subproton and electron scales (Sahraoui et al 2004;Mangeney et al 2006;Sahraoui et al 2006) and kinetic instabilities and nonlinear structures are present (Sahraoui et al 2004;Sahraoui 2008;Alexandrova et al 2008b). Major differences with the solar wind do exist, however, e.g., (i) magnetosheath turbulence evolves in a 'confined' space limited by the bow shock and the magnetopause and these boundaries may influence the anisotropy of the turbulence (Sahraoui et al 2006;Yordanova et al 2008), and, (ii) in contrast to the solar wind, the fluctuations are dominated by zero-frequency compressible fluctuations (e.g., mirror modes Sahraoui et al 2006). In a recent large survey of STAFF waveform data obtained in the magnetosheath, Huang et al (2014) quantified the differences in spectral slopes found in the solar wind and magnetosheath in the magnetic energy spectra between the ion and electrons scales (see Fig.…”
Section: Electron Scale Turbulencementioning
confidence: 99%
“…Indeed, only a handful of studies have been carried out in recent years (see e.g., Sahraoui et al 2003Sahraoui et al , 2004Mangeney et al 2006;Sahraoui et al 2006;Alexandrova et al 2008b;Yordanova et al 2008;He et al 2011). Two main similarities with solar wind turbulence emerged from those studies: the turbulence in strongly anisotropic (k k ⊥ ) at subproton and electron scales (Sahraoui et al 2004;Mangeney et al 2006;Sahraoui et al 2006) and kinetic instabilities and nonlinear structures are present (Sahraoui et al 2004;Sahraoui 2008;Alexandrova et al 2008b).…”
Section: Electron Scale Turbulencementioning
confidence: 99%
See 2 more Smart Citations